2017
DOI: 10.1128/jcm.01106-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Immunochromatography Technology Test (LDBio Diagnostics) To Detect Toxoplasma IgG and IgM: Comparison with the Routine Architect Technique

Abstract: A study comparing the ICT (immunochromatography technology) IgG and IgM rapid diagnostic test (LDBio Diagnostics, France) with a fully automated system, Architect, was performed on samples from university hospitals of Marseille and Saint-Etienne. A total of 767 prospective sera and 235 selected sera were collected. The panels were selected to test various IgG and IgM parameters. The reference technique, IgGII Western blot analysis (LDBio Diagnostics), was used to confirm the IgG results, and commercial kits Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 14 publications
4
22
0
Order By: Relevance
“…Different countries set their own healthcare priorities. Robust point-of-care testing, with high sensitivity and specificity and low costs, along with multiplexed testing for other congenital infections that are also treatable, including syphilis, hepatitis B, and HIV, currently in development, will further facilitate screening programs 70 , 82 , 83 . These measures will save lives, prevent expenditures, and reduce suffering, in addition to providing substantial spillover benefits for maternal, child, and family health 70 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different countries set their own healthcare priorities. Robust point-of-care testing, with high sensitivity and specificity and low costs, along with multiplexed testing for other congenital infections that are also treatable, including syphilis, hepatitis B, and HIV, currently in development, will further facilitate screening programs 70 , 82 , 83 . These measures will save lives, prevent expenditures, and reduce suffering, in addition to providing substantial spillover benefits for maternal, child, and family health 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The cost to developing countries will continue to increase if cases continue to increase and robust public health interventions are not implemented. Robust point-of-care testing with high sensitivity and specificity and low costs exists or is in development 70 , 82 , 83 . In between first trimester and end-of-gestation testing, Toxoplasma serology can be checked with newly developed, rapid POC tests, which are tractable, easy to use, and economical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the LDBIO test demonstrated 100% sensitivity and exhibited negligible false-positive results, it is advantageous for universal screening of Toxoplasma infection [35]. In short, the LDBIO POC test addresses the limitations of automated screening methods, i.e., not sufficiently sensitive for IgG detection and lack of specificity for IgM detection [42].…”
Section: Lateral Flow Assaymentioning
confidence: 99%
“…Point-of-care technology for antibody detection usually consists of immunochromatographic (ICT) membrane-based assays that can be performed without sophisticated laboratory infrastructure. Previous studies have shown optimal diagnostic performance for the Toxoplasma ICT IgG-IgM (LDBIO Diagnostics, Lyon, France) POC kit when compared with reference-serological methods in France [ 29 , 30 ] and the United States [ 31 ]. However, direct comparisons of performance of various POC kits against reference-standard methods used in the United States, where T gondii strains are more diverse, have not been previously performed.…”
mentioning
confidence: 99%